Controlled openness and foreign direct investment - Aizenman, Joshua 1949-; Yi, Sang-Seung (1997)
The purpose of this paper is to offer an explanation of why a developing country may adopt a partial reform under which foreign direct investments are controlled. We consider a country where the ruling elite [referred to as State capital] prevents the entry of Foreign capital and taxes the private sector before reform. The impetus to reform comes from an improved productivity of Foreign capital. The reform diminishes State capital's ability to tax the private sector but allows it to extract payment from Foreign capital for access to its markets. We show that a higher productivity of Foreign capital always increases the attractiveness of a partial reform under which State capital can control the inflow of Foreign capital. In contrast, a higher productivity of Foreign capital can reduce the attractiveness of a full reform under which the entry of Foreign capital is unregulated. Our analysis implies that, under the circumstances where the impetus to reform comes from improvements in Foreign productivity, State capital's exercise of control over Foreign capital's inflow may be a necessary condition for the reform to take place at all. In the absence of such a control, State capital may be reluctant to carry out the efficiency-enhancing reforms."
Keywords: Buitenlandse investeringen; Mathematisches Modell; International trade -- Mathematical models; Investments, Foreign -- Mathematical models